The Effect of Covid-19 Prevention Education on Public Mothers in Reducing Anxiety Level in The Time Covid-19 Pandemic - Liza Erviana Erviana; Ismarwati; Yuli Isnaeni (Jurnal Health Sains, 2022)
The COVID-19 pandemic has caused many restrictions on almost all routine services, both in terms of access and quality, including restrictions on maternal and neonatal health services, such as a reduction in the frequency of antenatal care and postponement of classes for pregnant women and the postpartum period, these conditions can cause problems globally. psychological problems for pregnant women postpartum, which can cause anxiety, if the mother's own anxiety is left untreated it will have an impact on mothers who will experience postpartum blues. Objective: To review COVID-19 prevention education for postpartum mothers in reducing anxiety levels. Methods: The method used is a scoping review using keywords, namely Population Exposure Outcame (Peos), namely population: post partum, education, and anxiety by (following the PRISMA Flow Chart guidelines, Result: By providing education on COVID-19 prevention in reducing levels postpartum mothers anxiety following anxiety skinning using the Hamilton Anxiety Rating Scale (HARS) and COVID-19 prevention education using video, able to stimulate the senses of hearing as well as vision so that mothers can understand them well with changes in knowledge, attitudes and skills of mothers before and after after being given education regarding prevention of COVID-19, Conclusion: factors that influence anxiety in postpartum mothers during the COVID-19 pandemic are stressors, maturity, age, education, environment, by conducting anxiety screening and providing education to postpartum mothers, it is hoped that it can reduce anxiety san as well as increasing knowledge related to postpartum mothers regarding the prevention of COVID-19 during the pandemic so that it does not cause anxiety.